Thirst trap : a novel - O'Hare, Gráinne (Crown Publishing Group, 2025)
"Harley, Râoise, and Maggie have been friends for ages. After meeting in primary school years ago, the women are still together, spending their nights on the sticky dancefloors of Belfast's grungiest pubs. Each woman is navigating her own tangle of entry-level jobs, messy romantic entanglements, and late nights, but they always find their way back to each other, and to the ramshackle house they share. And amidst the familiar chaos, the three are still grieving their fourth housemate, whose room remains untouched, their last big fight hanging heavily over their heads. The girls' house has witnessed the highs and lows of their roaring twenties--raucous parties, surprising (and sometimes regrettable) hook-ups, and hellish hangovers. But as they approach thirty, their home begins to crumble around them andthe fault lines in their group become harder to ignore. In the wreckage, they must decide if their friendship will survive into a new decade--or if growing up sometimes means letting go"--